EFFECTS OF NUMBER OF MAGNET IN HALBACH MAGNET SYSTEM FOR PRODUCING HOMOGENEOUS MAGNETIC FIELD - Dogan, N.; Inci, M.; Bingolbali, A.; Koten, H. (IEEE, 2015)
[No abstract available]
2015 5th International Workshop on Magnetic Particle Imaging (IWMPI) -- MAR 26-28, 2015 -- Istanbul, TURKEY